Penggunaan Media Sosial terhadap Pencegahan Penyebaran HIV/AIDS - Devi Harmita; Kusman Ibrahim; Urip Rahayu (Jurnal Keperawatan Silampari, 2022)
This study aims to determine a practical method approach to using social media to prevent the transmission of HIV/AIDS infection. The preparation of this literature review uses the narrative literature review method by entering keywords into the Pubmed, ProQuest, Wiley, CINAHL, and Science Direct databases. The study results indicate that the practical techniques used in the use of social media to prevent the transmission of HIV/AIDS infection include Network Monitoring System (NMS) and direct intervention. The Network Monitoring System (NMS) method can analyze the role of health sociology science on statistical data or social change trends used as consideration in formulating health promotion policies. Meanwhile, direct intervention with a comprehensive educational approach in empowering individuals or groups becomes a stimulant to self-potential to deal with health problems independently. In conclusion, both of them produce outputs in increasing awareness in the prevention and transmission of HIV/AIDS, healthy sexual knowledge, minimizing stigma against people living with HIV/AIDS, getting a target tracing flow that will be given education. Keywords: Social Media, Prevention and Control, HIV Infection